Stress Estimating of Unbound Granular Base Course - Siripun, Komsun; Jitsangiam, Peerapong; Nikraz, Hamid (Engineers Australia, 2010)
This study aims to report theoretically the possible approach of stress distribution on flexible pavement using the finite element method and laboratory results in order to expand additional concepts of analysis and design for Western Australian pavement through the mechanistic approach. As the effects of uniform design pressure and material attributes are generated when vehicles travel, stress and strain between tire and pavement layers were investigated. The conventional pavement diagram consists of a surfacing, base-course, sub-base and sub-grade.Test results showed that stress and strain were considerable underneath the wheel path and rutting and fatigue failure may set off from the top and bottom areas inside the ultimate stress layers. Nevertheless the maximum compressive stress indicated at the top horizontally is higher than twice the vertical path. As is well known, road surface rutting and fatigue is generally the main cause of deterioration in flexible pavements. In this study, the elastictoplastic theory.